2023
DOI: 10.1007/s13755-022-00197-5
|View full text |Cite
|
Sign up to set email alerts
|

MHA: a multimodal hierarchical attention model for depression detection in social media

Abstract: As a serious mental disease, depression causes great harm to the physical and mental health of individuals, and becomes an important cause of suicide. Therefore, it is necessary to accurately identify and treat depressed patients. Compared with traditional clinical diagnosis methods, a large amount of real and different types of data on social media provides new ideas for depression detection research. In this paper, we construct a depression detection data set based on Weibo, and propose a Multimodal Hierarch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The authors obtained a comprehensive and well-rounded annotation strategy to guide the categorization of social media users into individuals with an explicit diagnosis of EDs, healthcare professionals, communicators (i.e., those who communicate, exchange, and distribute information to the public), and non-ED individuals. The approaches above attempted to address the possibility of researchers overlooking implicit indicators of specific MH disorders or lacking sufficient clinical knowledge to make accurate inferences based on several posts created by each individual [ 135 , 189 ]. However, these efforts may not suffice, given that public content posted by individuals might be adapted with considerations of self-presentation factors.…”
Section: Resultsmentioning
confidence: 99%
“…The authors obtained a comprehensive and well-rounded annotation strategy to guide the categorization of social media users into individuals with an explicit diagnosis of EDs, healthcare professionals, communicators (i.e., those who communicate, exchange, and distribute information to the public), and non-ED individuals. The approaches above attempted to address the possibility of researchers overlooking implicit indicators of specific MH disorders or lacking sufficient clinical knowledge to make accurate inferences based on several posts created by each individual [ 135 , 189 ]. However, these efforts may not suffice, given that public content posted by individuals might be adapted with considerations of self-presentation factors.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the studies presented in the table emphasize the importance of considering multimodal data, user characteristics, and sentiment analysis for a comprehensive understanding of depression 80 , 81 . They also propose the use of lexicon features and emotional information capture to improve depression detection 82 , 83 .…”
Section: Resultsmentioning
confidence: 99%
“…The authors proposed a feature section method for analyzing depression symptoms using Multivariate time series approach, but the authors ended up with only correlating the disease to some of its symptoms. Li et al [26] built and deployed a multimodal attention mechanism for classifying social media users to depressed or normal users. The authors confirmed that analyzing the text data with picture added to it can lead to better results in depression detection, but this is not always the case on social media, beside some other drawbacks of their prosed solution such as the complexity and time consumed performing classification task.…”
Section: Literature Reviewmentioning
confidence: 99%